Dampak Sosial Ekonomi Pariwisata Terhadap Pedagang Souvenir Di Daya Tarik Wisata Pura Gunung Kawi Tampaksiring Gianyar - Ningsih, Ni Wayan Ariyoshi Sastra; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p04, 2018)
The tourism grows fastly and attract more villagers and local organization to develop tourism industry in order to get an income for their own region. It should give benefits for local people, government and investors. Tourism is an activity that involves the local community, and also bring impacts to them. One of the of tourism sector is socio-economic. Socio-economic impact of tourism is generally focus on the change of sales, incomes, and employments. This research has been conduct in Gunung Kawi Temple, Tampaksiring, Gianyar. This research aims to determine the socio-conomic impacts of tourism toward souvenir sellers who are part of local people. The data are collected through observation, interviews, questionnaires, and literature study. The results of this study show that tourism activities in Gunung Kawi Temple give positive impacts toward the job opportunity and a good response from the souvenir sellers. However, the tourism development also brings negative impacts toward the price of products, and it becomes cheaper. This happen because they compete to sell the similiar products. In addition, they have an unfriendly attitude to offer their products to the tourists. The managers of this tourist attraction (in this case are local people and government) should improve the design of souvenir kiosks to make it more clean and beautiful to tourists. They should give more trainingto the seller about good attitude of selling products. They also should give motivations to handicraft makers to make them keep innovate and invent new products, therefore the product will be more varieted.   Keywords: Socio-Economic Impact of Tourism, Souvenir Sellers, Gunung   Kawi Templ e